Projeto de bloco, acionamento de válvulas e sistema de lubrificação para motor monocilindro de pesquisa - Strapasson, Matheus (2024)
The new phases of PROCONVE regulations make vehicle emissions homologation a challenge. In this context, a promising technology is ultra-high pressure direct injection (UHPDI), which allows late injection, bringing benefits such as increased specific heat ratio and compressing only with air, preventing knock occurrence. When planning a research project to evaluate this technology, the demand arose to design a single-cylinder research engine. This work addresses the design of the crankcase, valve actuation, and lubrication system for this engine. Consequently, an evaluation of the state of the art was conducted based on research engines from leading companies in the market to identify important points to be considered in the design. The design of the main bearings was carried out in two stages: the conception of the geometry and the construction of a model for simulating the inertial forces and the minimum oil film thickness. The design of the crankcase focused on establishing the geometry, based on the analysis of interference between components, manufacturing tolerances, and the recommended dimensions for tapped holes. For the exhaust valve train, the design was based on the GSE-T4 engine, aiming to achieve the same lift and duration as this engine but with direct acting. Due to difficulties related to meeting the contact stresses between the cam and the follower, the lift had to be reduced, and the duration increased. For the intake, it was not possible to base the design on the GSE-T4 engine system because the variable lift and duration mechanism in this engine is complex, and without detailed information on this mechanism, the intake design would become time-consuming and costly. Therefore, intake operation maps of the GSE-T4 engine were obtained, and several intake camshafts with different durations and lifts were manufactured, each representing an operational range of the engine. Finally, the lubrication system architecture was based on the Ricardo Proteus engine, using the crankcase as a sump and several tubes connected to a distribution tube to guide the oil to the components. The design of this system included structural simulations of the distribution tube and 1-D fluid dynamic simulations for the oil circuit, concluding that a flow rate of 5,5 L/min with a pressure of 4 bar would be ideal for engine lubrication. After manufacturing the parts, the engine was assembled in the test cell, conducting tests with a port injection system. Despite identifying some areas for improvement, it was observed that the engine withstood the test conditions with stability and safety, fulfilling its primary purpose.